2011
DOI: 10.3904/kjim.2011.26.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Post-Transplant Bone Marrow Plasma Cell Percent in Multiple Myeloma Patients Undergone Autologous Transplantation

Abstract: Background/AimsAutologous stem cell transplantation (ASCT) has become the treatment of choice for patients with multiple myeloma (MM). Studies have shown that maintenance treatment with interferon-alpha is associated with improved survival rates following ASCT. However, despite these recent advances in regimes, relapses are inevitable; thus, the prediction of relapse following ASCT requires assessment.MethodsWe retrospectively analyzed 39 patients who received ASCT between 2003 and 2008. All patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…To the best of our knowledge, no quantitative data regarding the fat-signal fraction of vertebrae in plasma cell disorders have previously been presented. A report by Hwang et al [17] demonstrated that the median bone marrow plasma cell percent (BMPCp) at diagnosis of multiple myeloma was 43.0%, while the median BMPCp at post-treatment was 0.7%. The IDEAL sequence offers the possibility to noninvasively assess response to treatment by providing quantitative information about the conversion of myelomainfiltrated marrow to fat tissue.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, no quantitative data regarding the fat-signal fraction of vertebrae in plasma cell disorders have previously been presented. A report by Hwang et al [17] demonstrated that the median bone marrow plasma cell percent (BMPCp) at diagnosis of multiple myeloma was 43.0%, while the median BMPCp at post-treatment was 0.7%. The IDEAL sequence offers the possibility to noninvasively assess response to treatment by providing quantitative information about the conversion of myelomainfiltrated marrow to fat tissue.…”
Section: Discussionmentioning
confidence: 98%